2020
DOI: 10.1002/brb3.1621
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Zhong‐Yong thinking based dialectical behavior therapy group skills training versus supportive group therapy for lowering suicidal risks in Chinese young adults: A randomized controlled trial with a 6‐month follow‐up

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In adapting DBT to Nepal, the DBT concept of “Wise Mind” was described as a synthesis of heart–mind ( man ) and brain–mind ( dimaag ), and therapists de-emphasized culturally unfamiliar concepts such as the interpersonal goal of self-respect (Ramaiya et al, 2018). In a study in China, the DBT principle of dialectics was framed using the culturally familiar concept of golden mean ( zhong-yong) thinking, which is a philosophy derived from Confucianism that emphasizes pursuit of a middle ground (Yang et al, 2020). In implementing DBT with a Chinese international student, the therapist described emphasizing Chinese concepts of maintaining social harmony and respecting elders in the interpersonal effectiveness module (Cheng & Merrick, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In adapting DBT to Nepal, the DBT concept of “Wise Mind” was described as a synthesis of heart–mind ( man ) and brain–mind ( dimaag ), and therapists de-emphasized culturally unfamiliar concepts such as the interpersonal goal of self-respect (Ramaiya et al, 2018). In a study in China, the DBT principle of dialectics was framed using the culturally familiar concept of golden mean ( zhong-yong) thinking, which is a philosophy derived from Confucianism that emphasizes pursuit of a middle ground (Yang et al, 2020). In implementing DBT with a Chinese international student, the therapist described emphasizing Chinese concepts of maintaining social harmony and respecting elders in the interpersonal effectiveness module (Cheng & Merrick, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies mentioned challenges when skills groups were conducted in English when this was not the clients’ native language (Arunagiri, 2021; Cheng & Merrick, 2017)—for example, a client expressed frustration with not understanding nuances in terminology used to refer to certain emotions (Cheng & Merrick, 2017). Several studies mentioned that the interpersonal effectiveness module was especially difficult and at times incongruent with clients’ cultural contexts (Arunagiri, 2021; Cheng & Merrick, 2017; Ramaiya et al, 2018; Yang et al, 2020). Across studies, clients perceived that this module prioritized attainment of individual objectives over those of the group, whereas their cultural beliefs emphasized social cohesion and social goals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 44 eligible studies of interventions were identified from research conducted in 15 countries (online supplemental table 1). 24–67 Most studies were conducted in upper-middle-income (n=22; 50%) or lower-middle-income countries (n=13; 30%; table 2). Most studies were conducted in Asia: Bangladesh (n=1), China (n=7), India (n=8), Iran (n=14), Nepal (n=1), Pakistan (n=1), Sri Lanka (n=6) and Türkiye (n=1).…”
Section: Resultsmentioning
confidence: 99%
“…There are relevant reviews on the application of DBT in China. However, there are few intervention studies, and the targets of intervention are concentrated on suicidal selfinjury behavior and eating disorders (13,14). There are few studies on the application of DBT in college psychological consultation and counseling (emotion regulation), and there is a lack of localized programs and empirical analysis of DBT in China.…”
Section: Discussionmentioning
confidence: 99%